The Correlation Between Self-Efficacy and Preparedness of Community Health Center Nurses in Disaster Management Efforts - Kurnia, Theresia Avila; Rusmini, Rusmini; Emilyani, Desty; Wijayanti, Gusti Ayu Sri Puja Warnis (Jurusan Keperawatan, Poltekkes Kemenkes Mataram, 2025)
Indonesia is a disaster-prone country from a geographical, climatological, and demographic perspective. Its location between two continents and two oceans gives Indonesia high economic potential, yet also makes it vulnerable to disasters. Disasters always leave detrimental impacts, whether physical, psychological, or material. As the first line of response in a disaster, nurses must understand their role in disaster management and preparedness. Nurses are responsible for preparing themselves to gain the necessary knowledge and skills (competencies) to care for disaster victims and to achieve readiness for future disaster management. The purpose of this study is to analyze the correlation between self-efficacy and the preparedness of community health center nurses in disaster management efforts. The researcher used a descriptive analytical design with a cross-sectional approach. The target population was 30 community health center nurses, selected using a purposive sampling technique. The research instrument used was a standardized questionnaire. The statistical tests used were univariate and bivariate analyses with the Spearman's rho correlation test. The significance value for the disaster preparedness variable was found to be <0.05 (p=0.032), meaning the research hypothesis was accepted. This indicates that there is a correlation between the variable of disaster preparedness and the self-efficacy of nurses in facing disasters. A strong correlation between disaster preparedness and self-efficacy among community health center nurses confirms that improving preparedness through training and simulations will directly impact nurses' confidence in handling emergency situations